ACO-Based Optimal MIMO Sliding Mode Controller Design for a New Reconfigurable Unmanned Aerial Vehicle - Khedidja Bouhabza; Mohamed Guiatni; Yasser Bouzid; Mustapha Hamerlain (Engineering Proceedings, 2023)
The Optimized Multiple Inputs and Multiple Outputs Sliding Mode controller (MIMO-SMC) is intended to control the reconfigurable UAV, which can take on a variety of configurations while maintaining the efficiency of a conventional quadrotor in terms of hovering and precision handling. The Ant Colony optimization algorithm is used to calculate controller gains and to ensure optimal performance, such as small errors and lower energy consumption. The control goal is to allow the proposed UAV to track its trajectory for various configurations in the face of uncertain parameters to impose the position, altitude, and yaw angle while stabilizing its roll and pitch angles. Finally, simulation results are used to demonstrate the efficiency and performance of the proposed controller, and we calculate the energy consumption for each configuration.